Enhancing Prior Knowledge Development in English Language Education through Chat GPT-Assisted Learning - Fadillah, Ega Nur; Saridah, Siti; Kamilasari, Mila; Nur'aida, Ai; â Hafizudin, â Hafizudin; Kamilia, Adila; Sulaeman, Dedi (Universitas Pendidikan Mandalika, 2025)
This study investigates the potential of Chat GPT as a tool to develop students' prior knowledge in English language education. Recognizing the importance of foundational knowledge in effective language acquisition, this research explores how Chat GPT can support English language learners by pre-activating vocabulary, contextual understanding, and cultural awareness. Through a quasi-experimental design involving control and experimental groups, the study examines the effectiveness of Chat GPT-assisted learning activities compared to traditional methods. Participants in the experimental group receive customized pre-learning prompts and exercises generated by Chat GPT, aiming to bridge gaps in cultural and contextual understanding prior to formal instruction. Data is collected via pre- and post-tests, structured interviews, and observations to measure improvements in students’ readiness and comprehension. The findings highlight the impact of AI-driven tools on enhancing student engagement and knowledge acquisition in language education, offering practical insights into Chat GPT’s role in supporting differentiated instruction and personalized learning. This study contributes to pedagogical approaches by positioning Chat GPT as an adaptable, resource-efficient tool for language educators, especially in contexts where access to native English interaction is limited. The results provide evidence-based recommendations for integrating AI in classrooms, supporting instructional design and policy development for sustainable and inclusive education practices.